'Ulama And Umara In The Islamic Political System - Pebriana Lubis (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Politics in Islam is not a taboo/wrong thing, but has become one of the ways of Islamic da'wah since the time of the development of Islam. This study wants to narrate the role of ulama and umara in the Islamic political system. The methodology in this study uses a Study Library by collecting various references both offline and online. The purpose of this research is to explore the historical roots of the topics presented and make them as reflections and references for human thinkers. The important role 'Ulama (experts of science) play a major role when conveying the aspirations of the Islamic ummah and Umaro (Leader) as the holder of a policy, something that cannot be separated between the two, from the smallest thing to the biggest thing. it is also classified as “Mutualism Symbiosis” where when the 'Ulama makes a mistake in taking a policy, it's the 'Ulama who must put up a body in giving advice.